Development of Cosmetic Treatments Based on Chemistry, Laser, and Biotechnology: An Integrated Study on the Effects of Active Compounds on Skin Cell Regeneration - Mutib, Jaafar Jassim Marzouk; Hasan, Fatimah Ali; Alawadi, Zahraa Hussein Ali Mahdi; Eidan, Hawraa Shahid Shakir (American Journal of Biomedicine and Pharmacy, 2025)
Cosmetic products for skin regeneration typically target keratinocytes and fibroblasts, but conventional formulations allow limited penetration and bioavailability. In integrated protocols, Chemistry, Laser, and Biotechnology approaches synergistically enhance skin penetration and action, potentially improving regeneration efficacy. Chemistry contributions encompass formulation and delivery technology to optimize active compound design and incorporation. Laser-based strategies exploit laser principles to augment the influence of active compounds. Biotechnological innovations, encompassing cell-based, biomaterial, and gene-modified approaches, complement active-compound therapies. An integrated protocol uniting the three modalities is envisioned, with Chemistry, Laser, and Biotechnology interactions forming the foundation for future personalizable regimens.